Diamagnetic Spectra of Alkaline Earth Barium in a Magnetic Field (Journal of Atomic and Molecular Sciences, 2018)
We present theoretical diamagnetic spectra of Barium using R-matrix method combined with quantum defect theory. The nonhydrogenic character of the spectra is analyzed for Ba. Comparisons are made with similar calculations for hydrogen and with data of  experiments in the l-mixing region and n-mixing region. The result shows that the theoretical results are in good agreement with the experimental ones.
Keywords: diamagnetic spectra; R-matrix.